Signal Processing for Noise and Online Force Modeling Detection for a Robot Hand Based on EtherCAT Communication. Issue 1 (2nd January 2016) - Hou, Mingxin; Jiang, Li; Liu, Hong; Chen, Zhaopeng
Abstract: This study proposes three efficient algorithms for online computing of fingertip force modeling and noise involved in 1-D, 2-D and 3-D models. Fast and effective real-time detection for fingertip force modeling is extremely important for successful manipulation on an object by a robot hand in a real situation. Meanwhile, signal processing for a desired force signal is necessary if unwanted signals and noise cannot be ignored in practical applications. Butterworth low-pass filters designed in this study can be effectively used for filtering noise and obtaining flatter and smoother force modeling detection signals. An EtherCAT slave circuit is designed and force detection models using Beckhoff TwinCAT 3.1 provide feedback signals. The calculation is made during several real-time experiments.